2018
DOI: 10.1002/rcm.8039
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the source of methomyl using stable isotope analysis

Abstract: This study demonstrates the potential of stable isotope ratio analysis for the determination of insecticide origin in fatal poisoning cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The carbon and nitrogen isotope ratios were then measured by IRMS. The 13 C/ 12 C and 15 N/ 14 N isotope ratios are expressed as δ 13 C and δ 15 N values per mill (‰) relative to Vienna Pee Dee Belemnite (VPDB) and air, respectively 21 …”
Section: Methodsmentioning
confidence: 99%
“…The carbon and nitrogen isotope ratios were then measured by IRMS. The 13 C/ 12 C and 15 N/ 14 N isotope ratios are expressed as δ 13 C and δ 15 N values per mill (‰) relative to Vienna Pee Dee Belemnite (VPDB) and air, respectively 21 …”
Section: Methodsmentioning
confidence: 99%
“…It improves the detection of the isotope values of specificity in the compound of interest. A recent study by Song et al [ 84 ] also showed the great potential of using stable isotopes to trace the source of methomyl in murder cases caused by methomyl as poison, which is unaffected by methomyl metabolite (i.e., methomyl oxime) using GC-IRMS. A methomyl, a prohibited insecticide, is highly toxic and is often used for self-poisoning and sometimes for poisoning of murder convicts [ 98 , 99 ].…”
Section: Applications Of Csia For Monitor Pesticide Pollution In Environments and Agricultural Productsmentioning
confidence: 99%
“…In 2016, in the process of investigating deaths from drinking alcohol with added methomyl, a forensic research team was able to find a suspect with a pesticide with the same carbon-stable isotope value of methomyl in the alcohols. The stable value of the methomyl carbon isotope served as a ‘smoking gun’ to find suspects, and this study also presented results on fractionation in the process of obtaining evidence, such as no changes in isotope ratio on the influence of intestinal pH [ 84 ]. These interesting examples support the possibility of the differentiation of pesticides through differences in isotopes in raw materials and composition.…”
Section: Applications Of Csia For Monitor Pesticide Pollution In Environments and Agricultural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotope analysis has been used to trace the source of methomyl, 93 as the degradation products of carbamate pesticides are generally non-toxic substances such as NH 4 − , SO 4 2− , and CO 2 . Isotopic fractionation during CSIA can be used to determine the type of reaction that triggers the degradation of a contaminant, specifically by describing the chemical bond changes in the reaction pathway.…”
Section: Pesticide Categories and Csia Technologymentioning
confidence: 99%